2007
DOI: 10.1016/j.juro.2007.05.134
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Renal Cell Carcinoma With Tumor Thrombus Extension

Abstract: Eastern Cooperative Oncology Group performance status, metastatic status, sarcomatoid features and concomitant perinephric fat invasion are the most powerful prognostic factors of survival in renal cell carcinoma with tumor thrombus extension. Our data indicate that a redefinition of the current T3 classification may improve its predictive accuracy. We propose that T3 renal cell carcinoma with fat invasion or thrombus extension alone should be classified as T3a, while that with thrombus extension plus fat inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
108
3
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(127 citation statements)
references
References 17 publications
11
108
3
5
Order By: Relevance
“…Fuhrman grade is currently the most widely used grading protocol in North America and Europe, and higher grades are correlated with tumor aggressiveness and increased metastatic potential (23,24). The prognostic significance of histological grade in patients with RCC and venous tumor thrombus is controversial (4,(6)(7)(8)16,25). In our study, Fuhrrnan grade was found to be one of most important prognostic factors for survival and relapse in patients with RCC and venous tumor thrombus, supporting the role of histological grade as an important predictor of patient outcomes.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Fuhrman grade is currently the most widely used grading protocol in North America and Europe, and higher grades are correlated with tumor aggressiveness and increased metastatic potential (23,24). The prognostic significance of histological grade in patients with RCC and venous tumor thrombus is controversial (4,(6)(7)(8)16,25). In our study, Fuhrrnan grade was found to be one of most important prognostic factors for survival and relapse in patients with RCC and venous tumor thrombus, supporting the role of histological grade as an important predictor of patient outcomes.…”
Section: Discussionsupporting
confidence: 64%
“…In our study, the 2-, 5-and, 10-year CSS rates of all patients and those with non-metastatic RCC were 64.2%, 47.1% and 31.7%, and 80.9%, 64.5% and 44.9%, respectively. These rates appear to be a little higher than those of most reports from Western countries (3)(4)(5)7,8,16). However, our patient population included a higher proportion of individuals with tumor thrombus extension into renal vein only than other studies except for the one by Wagner et al, and may explain these seemingly higher survival rates (16).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…98 In subsequent studies conflicting results as to the prognostic significance of this classification have been reported, with some studies validating the classification, [99][100] whereas others have shown that the level of tumor thrombus beyond the renal vein does not influence survival. [101][102][103][104][105] To predict the outcome more accurately in locally advanced disease, additional parameters have been proposed to further stratify tumors showing vascular invasion. In particular, the poor prognosis associated with perirenal fat, adrenal and Gerota's fascia infiltration has led to the incorporation of those features into a proposed modification of pT3-4 criteria.…”
Section: Regional Spread Of Tumor (Tnm Category T3)mentioning
confidence: 99%
“…In particular, the poor prognosis associated with perirenal fat, adrenal and Gerota's fascia infiltration has led to the incorporation of those features into a proposed modification of pT3-4 criteria. 92,101,106 In this modification, which is based on international multicenter studies, cases have been grouped according to the presence of tumor thrombus within the renal vein or infradiaphragmatic vena cava, or the presence of perirenal fat invasion (group 1), fat invasion with either renal vein or infradiaphragmatic vena cava thrombus, or adrenal gland invasion (group 2) and adrenal involvement with either renal vein or infradiaphragmatic vena cava thrombus, or supradiaphragmatic vena cava thrombus or Gerota's fascia invasion (group 3) with 5-year survivals for each group being shown to be 61, 35, and 12.9%, respectively. 106 Although this would seem to be a promising advance, further studies and necessary to validate this proposed modification of the TNM system.…”
Section: Regional Spread Of Tumor (Tnm Category T3)mentioning
confidence: 99%